Political Science at the LSE A History of the Department of Government, from the Webbs to Covid - Schonhardt-Bailey, Cheryl; Bannerman, Gordon (Ubiquity Press, 2021)
This monograph traces the emergence and evolution of the LSE Government Department from 1895 to 2020, focusing on the personalities that guided the development of the Department, the social and political contexts the Department existed within, its research agenda and course structure, and the location of the Department in British politics. It also charts the evolution of the discipline of political science in Britain itself. The volume is divided chronologically into four chapters, each covering roughly similar time periods in the Department's history and focuses on the events that shaped it: personalities, events, and location. Key themes are the development of political science in Britain, the impact of location on the LSE Government Department, the professionalisation of academia in Britain, and the microcosm the Department presents of British political life during each time period. The conflicts between progressive and conservative forces are a recurring theme which helps link the internal dynamics of the Department with the wider social and political contexts that occurred from the beginning of the School to its 125th anniversary. The volume uses detailed archival research, particularly in the early chapters, as well as over thirty interviews with a range of individuals with unique perspectives on the Department. These include current and former faculty and students (ranging from academics such as Christopher Hood, Anne Phillips and Tony Travers, to graduates who have subsequently become politicians-such as Anneliese Dodds, former UK Shadow Chancellor of the Exchequer, and Kennedy Stewart and Michael Fougere, both mayors in Canada), as well as others with strong links to the Department, such as Meghnad (Baron) Desai, and Professors Tim Besley and Nick Barr. This monograph offers a wealth of insights on the history of political science not only at the LSE, but in British academia more broadly. It speaks to a wide historical and social science audience concerned with Fabian and socialist history, the history of politics and education, and the development of British political science. Of course, it also offers appeal to more immediate audiences, such as prospective and current students, alumni, and others throughout the wider LSE community. As a history of the LSE, as well as of the development of British higher education, it serves as both a specific case study and a general representative of wider trends within universities during the twentieth and early twentieth-first centuries. A unique feature of this monograph is that it represents the collective efforts of students from the LSE Government Department (including undergraduate, MSc and PhD), who worked under the leadership of Professor Cheryl Schonhardt-Bailey (Head of Government Department) and Dr Gordon Bannerman (British Historian). This collaboration has enabled a rich array of perspectives on the history of the Department but has also brought the monograph to life with personal ties to the Department itself.